Tłumacz – archeolog słodyczy - Pieciul-Karmińska, Eliza (Investigationes Linguisticae, 2012)
The articles discusses the problem of translation of lexical units referring to sweets on the example of the Polish translation series of E. T. A. Hoffmann’s world famous story Nutcracker. The first part of the article contains a short description of the significance of author’s lexical choices concerning sweets produced in the 19th century. In the second part a case study of the translation of the term “Devisen-Figuren” is presented. The third part shows the wide range of detailed descriptions used in the original text and their (more or less successful) transfer into Polish. The fourth part presents a specific case of a contemporary adaptation transforming all sophisticated sweets of the past into modern chocolate products. In the conclusions it is shown that translators’ fidelity on the lexical level means fidelity as a global approach to the original text.